2009
DOI: 10.1038/emboj.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

MAPKAP kinase MK2 maintains self-renewal capacity of haematopoietic stem cells

Abstract: The structurally related MAPK-activated protein kinases (MAPKAPKs or MKs) MK2, MK3 and MK5 are involved in multiple cellular functions, including cell-cycle control and cellular differentiation. Here, we show that after deregulation of cell-cycle progression, haematopoietic stem cells (HSCs) in MK2-deficient mice are reduced in number and show an impaired ability for competitive repopulation in vivo. To understand the underlying molecular mechanism, we dissected the role of MK2 in association with the polycomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Following stress stimulation, MK2/3 phosphorylate components of the complex, such as BMI1, a protein involved in the selfrenewal of hematopoietic stem cells. Interestingly, a recent study demonstrated that hematopoietic stem cells in MK2-deficient mice are reduced in number and show an impaired ability for competitive repopulation in vivo (320).…”
Section: Mk2/3mentioning
confidence: 99%
“…Following stress stimulation, MK2/3 phosphorylate components of the complex, such as BMI1, a protein involved in the selfrenewal of hematopoietic stem cells. Interestingly, a recent study demonstrated that hematopoietic stem cells in MK2-deficient mice are reduced in number and show an impaired ability for competitive repopulation in vivo (320).…”
Section: Mk2/3mentioning
confidence: 99%
“…Notably, PcG factors have been reported to be linked with RA, FGFs, SHH and MAP kinase pathways (Schwermann et al, 2009;Shi et al, 2014;van der Velden et al, 2012;Wu et al, 2013;Yokobayashi et al, 2013). By such interactions with signaling pathways, PcG factors may contribute to the compartmentalization of outgrowing or enlarging fetal tissues by regulating the expression of developmental genes.…”
Section: Discussionmentioning
confidence: 99%
“…But not only the composition of the complex is decisive. PRC1 is also regulated by external MAKPK kinases such as Mapkap2 (MK2) to improve the balancing between HSC self-renewal and differentiation [45].…”
Section: Resultsmentioning
confidence: 99%